Effect of Additives on Electrodeposition of Copper in Ch Cl-Gl A Low Eutectic Solvent - LIU Yang, HAO Jianjun, YIN Hongkun, WANG Xinhui (Cailiao Baohu)
The use of additives facilitates the deposition of copper on metal substrates.In this work，using choline chloride glacial acetic acid(Ch Cl-Gl A) as a low eutectic solvent and copper acetate as the main salt， the effects of ascorbic acid(C6H8O6)， disodium ethylenediamine tetraacetic acid(EDTA-2Na) and diethylenetriaminepentaacetic acid(DTPA) as additives on electrodeposition of copper on iron substrate were investigated.Electrochemical behavior was studied by cyclic voltammetry (CV) and chronoamperometry (CA)； scanning electron microscopy(SEM) and X-ray diffraction(XRD) were used to observe and analyze the morphology and composition of the coating.The UV-visible absorption spectrum of the complex formed in the electrodeposited solution with different additives was analyzed by a UV-Vis-NIR spectrophotometer.Results indicated that in Ch Cl-Gl A， the electrodeposition of copper involved two steps of oxidation-reduction with the first step of Cu2＋→Cu＋and the second step of Cu＋→Cu.All three additives promoted the deposition of copper in Ch Cl-Gl A，and ascorbic acid had the best effect，which could obtain a copper coating with good performance at room temperature.The electrodeposition of copper in Ch Cl-Gl A followed a three-dimensional instantaneous nucleation process and was an irreversible reaction controlled by diffusion.Moreover，the diffusion coefficients of Cu2＋and Cu＋could reach 4.003 9×10－7 cm2/s，4.762 7×10－7 cm2/s，respectively.The copper crystal prepared with ascorbic acid as additive was a polygonal sheet-like structure with distinct grains，and the optimal crystal plane was the (111) crystal plane.Besides，the average grain sizes of the copper layer with additives DTPA，EDTA-2Na and C6H8O6 were 50.71，55.12 and 52.73 nm.The average grain size of the copper layer without additive was 44.73 nm.